The Impact of Self-Questioning on the Achievement and Motivation of Fourth-Grade Science Students in Physics (Journal of the College of Basic Education, 2026)
The current research aims to know the effect of self-questioning strategy on the achievement of fourth-grade science students in physics and their motivation to learn the subject. To achieve the research objectives, the null hypotheses were formulated and an experiment was conducted that lasted a full semester, which is the first semester. The study was limited to fourth-grade science students in preparatory and secondary day schools affiliated with the Anbar Education Directorate (center) for the academic year (2024-2025), and the subject (the second, third and fourth chapters of the physics book for the fourth grade science). The research sample numbered (58) students in Al-Shumoukh Intermediate School for Boys for the academic year (2024-2025). Equivalence between the research groups was confirmed through variables (age in months, previous information, intelligence and a scale of motivation to learn the subject). The requirements for the experiment were prepared by constructing an achievement test due to the lack of appropriate tests for the purposes of the research, and preparing a scale of motivation to learn physics for the fourth grade science. The psychometric properties of both the achievement test and the scale of motivation to learn the subject were confirmed. After the students completed studying all the vocabulary required for the fourth-grade science physics course, the two research groups were tested using the prepared tools. Analyzing the data revealed that the experimental group students outperformed the control group in achievement and motivation to learn the material. In light of these results, a set of recommendations and suggestions were developed regarding the self-questioning strategy, which can be used in other educational institutions